2014
DOI: 10.5194/angeo-32-77-2014
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial aurora: astrophysical laboratory for anomalous abundances in stellar systems

Abstract: Abstract. The unique magnetic structure of the terrestrial aurora as a conduit of information between the ionosphere and magnetosphere can be utilized as a laboratory for physical processes at similar magnetic configurations and applied to various evolutionary phases of the solar (stellar) system. The most spectacular heliospheric abundance enhancement involves the 3 He isotope and selective heavy elements in impulsive solar flares. In situ observations of electromagnetic waves on active aurora are extrapolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Singly-ionized species usually can only be present in the Earth's ionosphere where the density is low but collision rates still sufficiently high. Large-scale geomagnetic storms and aurorae may cause anomalies to the ionospheric abundance and add extra transmission absorptions from Fe, Mg, or Si, for example (Roth 2014). It has been suggested that the amount of sodium in the upper Earth atmosphere can be temporarily increased by meteoritic deposition (Moussaoui et al 2010).…”
Section: Penumbral Spectramentioning
confidence: 99%
“…Singly-ionized species usually can only be present in the Earth's ionosphere where the density is low but collision rates still sufficiently high. Large-scale geomagnetic storms and aurorae may cause anomalies to the ionospheric abundance and add extra transmission absorptions from Fe, Mg, or Si, for example (Roth 2014). It has been suggested that the amount of sodium in the upper Earth atmosphere can be temporarily increased by meteoritic deposition (Moussaoui et al 2010).…”
Section: Penumbral Spectramentioning
confidence: 99%